What predicts workplace self-paced e-learning outcomes?: an exploratory study of motivation, self-regulated learning characteristics, and organisational contextual factors - Chau, Yat Kwong (2018)
Organisations today are investing significant amounts of time, money, and resources on workplace self-paced e-learning, yet employees seem to be having problems even getting these e-learning courses completed, bringing into question the true value of workplace self-paced e-learning. In an attempt to improve understanding of factors contributing to success in workplace self-paced e-learning, this study investigated how employee learners’ motivation, self-regulated learning, and organisational contextual factors affected outcomes in workplace self-paced e-learning. A quantitative study was conducted to investigate the research questions. Participants of the study were 119 employees enrolled in workplace self-paced e-learning courses provided by Hong Kong organisations. Data were collected using online questionnaires and analysed using the partial least squares structural equation modelling technique.